2019
DOI: 10.9734/jeai/2019/v31i330073
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Morpho-biochemical Traits Associated with Pod Borer (Helicoverpa armigera) Resistance in Pigeonpea Pods

Abstract: Pigeonpea contributes to food and nutrition security among poor households in urban and rural areas. Globally it is characterized by stagnant and unstable yield due to its susceptibility to various stresses including the pod borer (Helicoverpa armigera) which causes substantial damage to the crop and may result in absolute economic yield loss. The existing cultivated pigeonpea are susceptible to pod borer with only a few genotypes reported to be tolerant based on pod and seed damage. Limited information is ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…These findings indicate that higher phenol content is associated with reduced pod damage by pod borers in field conditions. The results reported in these studies are consistent with findings from Cheboi et al, (2019) [2] , who also observed a significant negative correlation between total phenol content and pod damage, with a correlation coefficient of -0.923**. This further supports the notion that phenolic compounds play a crucial role in mediating resistance against pod borers in legume crops.…”
Section: B Total Phenols (Mg/g)supporting
confidence: 91%
“…These findings indicate that higher phenol content is associated with reduced pod damage by pod borers in field conditions. The results reported in these studies are consistent with findings from Cheboi et al, (2019) [2] , who also observed a significant negative correlation between total phenol content and pod damage, with a correlation coefficient of -0.923**. This further supports the notion that phenolic compounds play a crucial role in mediating resistance against pod borers in legume crops.…”
Section: B Total Phenols (Mg/g)supporting
confidence: 91%
“…The protein content of the pods revealed a non-significant association with the per cent pod damage of H. armigera (Table 1). However, Cheboi et al (2019) reported significant positive correlation of seed crude protein with pod damage in pigeonpea. The reducing sugar content of the pods was higher than of seeds; in pod walls, it was observed to be minimum with IVT-705 (7.70%), followed by IVT-208 (8.12%) whereas, IVT-1-903 (12.36%) contained maximum; while the seeds sugar content was maximum with IVT-703 (18.36%) and minimum with IVT-705 (11.63%).…”
Section: Resultsmentioning
confidence: 92%
“…Green pods are used for vegetable purposes while dried peas are used as pulses (Tanuja and Kaith, 2020). Pigeon pea is a legume reported to contain 20-30% protein, 1.2% fat, 65% carbohydrate and 3.8% ash (Karri and Nalluri, 2017;Cheboi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%